DECISION OF SIGN OFF PREMATURE BASED ON AUDIT RISK AND TIME BUDGET PRESSURE BY THE PUBLIC ACCOUNTANT FIRMS IN EAST KALIMANTAN - Anisa Kusuma Wardani (Journal of Economics, Business, and Accountancy Ventura, 2013)
Based on the urgency of the professional auditor in providing the auditor's opinion in EastKalimantan, some previous researchers state that time budget pressure has a significant andpositive effect on sign off premature, and audit risk has a positive and significant effect onthe sign off premature, then the auditor will take highest audit risk if doing premature terminationof the audit procedures. This study surveys the 45 perpetrators of the practice of publicaccounting in the province using technical analysis regression. The results showed thatthe risk of audit and time budget pressure have a significant and positive effect on the decisionsign off premature, because it indicates any misstatement of the auditor for audit riskinformation. Thus, this condition can speed up the decision of premature sign off.